Navigating P2Y12 inhibition in the labyrinth of cardio-oncology care: cangrelor bridging in patients with cancer - Ali, Abdelrahman; Jewani, Poonam; Bourdillon, Max; Koutroumpakis, Efstratios; Khalaf, Shaden; Charitakis, Konstantinos; Thompson, Kara; Marmagkiolis, Konstantinos; Deswal, Anita; Iliescu, Cezar (Frontiers in Cardiovascular Medicine, 2024)
Cangrelor, a potent intravenous P2Y12 platelet inhibitor, has demonstrated effectiveness in reducing ischemic events without a corresponding increase in severe bleeding during percutaneous coronary intervention, as evidenced by the CHAMPION-PHOENIX trial. Its off-label role as a bridging antiplatelet agent for patients facing high thrombotic risks who must temporarily stop oral P2Y12 inhibitor therapy further underscores its clinical utility. This is the first case series to shed light on the application of cangrelor in cancer patients needing to pause dual antiplatelet therapy for a range of medical interventions, marking it as a pioneering effort in this domain. The inclusion of patients with a variety of cancer types and cardiovascular conditions in this series underlines the adaptability and critical role of cangrelor in managing the dual challenges of bleeding risk and the need for uninterrupted antiplatelet protection. By offering a bridge for high-risk cancer patients who have recently undergone percutaneous coronary intervention and need to halt oral P2Y12 inhibitors temporarily, cangrelor presents a practical solution. Early findings indicate it can be discontinued safely 2-4 h before medical procedures, allowing for the effective reintroduction of oral P2Y12 inhibitors without adverse effects. This evidence calls for expanded research to validate and extend these preliminary observations, emphasizing the importance of further investigation into cangrelor's applications in complex patient care scenarios.